Negativity bias for sad faces in depression: An event-related potential study - Dai, Qin; Wei, Juanjuan; Shu, Xiaorui; Feng, Zhengzhi (Clinical neurophysiology, 2016)
•Clinical depression has lower scores and greater N1 amplitudes for sad faces.•Sub-clinical depression has lower scores and greater P2 amplitudes for happy faces.•Cognitive and cerebral evidence show negativity bias in valence rating in depression. Negativity bias in depression has been previously confirmed. However, mainly during a valence category task, it remains unclear how happy or unhappy individuals perceive emotional materials. Moreover, cerebral alteration measurements during a valence judgment task is lacking. The present study aimed to explore a valence judgment of a valence rating task, combined with event-related potential (ERP) recording. Healthy controls, individuals with sub-clinical depression, and patients diagnosed with major depressive disorder (MDD) were recruited. Twenty-four subjects in each group completed a valence rating task, during which the ERP amplitudes were recorded. The MDD group had lower valence scores, faster responses, and greater N1 amplitudes for sad faces, whereas individuals with sub-clinical depression had faster responses and greater P1 amplitudes for all faces but lower valence scores and greater P2 amplitudes for happy faces. The findings suggest the tendency toward a negativity bias in valence ratings in patients with depression supported by behavioral and cerebral evidence, which is a latent trait of depression, possibly associated with the vulnerability of depression. The current study offers the first experimental evidence of cognitive and cerebral biomarkers of negativity bias in valence ratings in depression, which confirms Beck’s cognitive theory and gives important direction for clinical therapy.